Husband’s behavior and early marriage as risk factors for hepatitis B virus infection among pregnant women in Karangasem, Bali, Indonesia - Surapathi, I.N. Adnyana; Wirawan, Dewa Nyoman; Sawitri, Anak Agung Sagung (Universitas Udayana, 2021)
Background and purpose: Indonesia is categorized as a country with moderate level of hepatitis B virus (HBV) infection, where the majority of HBV transmissions occur from mother to child, horizontal transmission during childhood and adulthood, and transmission in health services. This study aims to determine factors associated with HBV infection among pregnant women. Methods: A case control study was conducted among 80 pregnant women with sero-positive HBsAg as cases and 80 pregnant women with sero-negative HBsAg as controls. The sources of cases and controls were the registers of pregnant women at 12 public health centers (PHCs) and Karangasem District Hospital from June 2017 to December 2018. Cases were selected by systematic random sampling from 129 pregnant women with sero-positive HBsAg and controls were selected through the same method from 1,408 pregnant women with sero-negative HBsAg. They were then matched based on village or residence. Data collected were including history of marriage, pregnancy, childbirth and abortion, history of health services relevant to HBV infection, use of contraception, mobility, permanent tattoos and history of injecting drug use. Data collection was carried out from June to August 2019 through face-to-face interviews with pregnant women as respondents in their respective homes using a pre-tested questionnaire. Bivariate data analysis was conducted with chi square test and multivariate analysis with logistic regression. Results: The case and control groups were similar in terms of age, number of pregnancy and parity. Risk factors which found to be significantly associated with HBV infection in pregnant women were age at first marriage <19 years with AOR=2.51 (95%CI: 1.13-5.60), history of husband’s mobility with AOR=3.07 (95%CI: 1.13-8.34), husband has a permanent tattoo with AOR=2.77 (95%CI: 1.04-7.44) and low level of maternal education with AOR=2.47 (95%CI: 1.06-5.73). Conclusion: Young marital age, low education, husband’s mobility and husband with permanent tattoos increase the likelihood of HBV infection among pregnant women. The coverage of HBV examination among pregnant women and early detection of HBV among husbands ought to be increased, especially among those with associated risk factors.